“KULAK NEMPIL” IN THE METHOD OF DETERMINING THE SELL PRICE CRACKERS RAW BLITAR MARKET - Irma Ayu Rahmawati; Diana Elvianita Martanti (Universitas Islam Balitar, 2020)
This research was conducted at the Raw Crackers Shop in Legi Market on March 1, 2019 to May 31, 2019. This study aims to analyze the crackers method and determine the selling price of the crackers. The research method used is descriptive qualitative method. The results of this research are traders to get goods when the stock of goods in the warehouse from the producers runs out, namely the kulak method. Kulakan that is applied is